Grammatical Errors in Writing Assignments among the Non-Field of Malay Language Students at University - Unjong, Bryan Kaba; Banseng, Saripah; Jimbai, Jackson (Universitas Negeri Padang, 2025)
The objective of this study is to identify grammatical errors, analyse the factors of grammatical errors and explain the preventive measure for writing assignments among non-field of Malay Language students at Sultan Idris University of Education. This study employed a qualitative research which utilizes five distinct assignment types from non-language disciplines as primary data sources and engages five grammar experts, comprising educators or instructors, as key informants. The findings reveal a non-field Malay Language students to commit errors in spelling, sentence structure, and word formation. Furthermore, the identified factors encompass both internal and external influences. Internally, students exhibit a limited grasp of grammar and encounter inadequacies in grammar instruction at the university level, while externally, factors such as social media, linguistic contamination, translation applications, and informal conversations contribute to these errors. In terms of recommendations of preventive measure, three specific steps are delineated: students must cultivate awareness and persistently strive for grammatical proficiency, intensify practice efforts, and establish supplementary classes dedicated to grammar refinement. This study carries substantial implications for educators and non-field Malay Language students alike, serving as a valuable resource for averting grammatical errors and enabling educators to formulate more efficacious teaching methodologies for addressing such issues.